1999
DOI: 10.1103/physreva.59.1070
|View full text |Cite
|
Sign up to set email alerts
|

Quantum nonlocality without entanglement

Abstract: We exhibit an orthogonal set of product states of two three-state particles that nevertheless cannot be reliably distinguished by a pair of separated observers ignorant of which of the states has been presented to them, even if the observers are allowed any sequence of local operations and classical communication between the separate observers. It is proved that there is a finite gap between the mutual information obtainable by a joint measurement on these states and a measurement in which only local actions a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
1,281
1
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,050 publications
(1,298 citation statements)
references
References 38 publications
11
1,281
1
5
Order By: Relevance
“…An entanglement is known to be very fragile to a local noisy channel. Furthermore, it was shown that a quantum state without entanglement contains non-locality [3]. L. Henderson and V. Vedral [4] suggested a method to obtain a classical correlation between parties.…”
Section: Introductionmentioning
confidence: 99%
“…An entanglement is known to be very fragile to a local noisy channel. Furthermore, it was shown that a quantum state without entanglement contains non-locality [3]. L. Henderson and V. Vedral [4] suggested a method to obtain a classical correlation between parties.…”
Section: Introductionmentioning
confidence: 99%
“…For example, [1,2,3,4] discuss whether entanglement is necessary for quantum computation, [5] shows nonlocality without entanglement, and [6,7] discuss how much of the information carried by various quantum states is actually classical. We extend this discussion into another domain: quantum cryptography.…”
mentioning
confidence: 99%
“…Nevertheless, the characterization of MES can be achieved as follows. The fact that LOCC protocols are strictly included in SEP [21] implies that if a state is not reachable (or convertible) deterministically via SEP it is also not reachable (or convertible) deterministically via LOCC. Hence, a state that is not reachable via SEP has to be in the MES.…”
Section: Theoremmentioning
confidence: 99%
“…They consist of enlarging the set of allowed operations such that one obtains classes of operations that are easier to deal with mathematically as for example PPT preserving maps [19] or separable transformations (SEP) (see [20] and references therein). As it will be important for our discussion we will focus here on SEP. LOCC is strictly included in SEP [21], i.e. any LOCC transformation corresponds to a completely positive trace-preserving map Λ whose action on any density matrix ρ can be written as Λ(ρ) = i X i ρX † i where…”
Section: Preliminariesmentioning
confidence: 99%